Answers

2016-06-15T03:03:35+08:00
Formula of nth term for arithmetic progression is
Tn = a1 + (n-1)d
Tn is the nth term
a1 is the first term
n is the exponent 
d is the common difference
Example
from your given you want to get the 5th term 
so
5th = 3 + (5-1)1
      = 3 + 4(1)
      = 7
so the 5th term is 7 !
0
  • Brainly User
2016-06-15T08:48:58+08:00
To get the nth term of the given sequence: 3, 4, 5, 6, 7, ..., find its rule.

an = a₁ + (n-1)(d)

a₁ = 3     d = 1 (common difference)

an = 3 + (n-1) (1)
an = 3 + n - 1
an = n + 2

ANSWER: an = n + 2
0